KORELASIANTARA VITALITAS PSIKIS DAN KOMPETENSIPSIKOMOTOR DENGAN KOMPETENSI KOGNITIF MATA PELAJARAN BIOLOGI SMA NEGERI 2 SRAGEN (RELATIONSHIP AMONG THE PSYCHOLOGICAL VITALITY AND PSYCOMOTOR COMPETENCE WITH THE COGNITIVE COMPETENCE ON BIOLOGY OF SMAN 2 SRAGEN) - ROHMI MARLINA; ALVI ROSYIDI; HARLITA HARLITA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2006)
This research was carried out upon the X grade student of SMA Negeri 2 Sragen. This research were aimed to find the correlation between psychic vitality and cognitive, correlation between psychological competence and psychomotor competence with cognitive competence on biological learning and the dominant contribution for each independent variable to cognitive competence on biological learning. This is a descriptive-quantitative research with ex post facto. The population of the study is the X grade of SMA Negeri 2 Sragen in academic year of 2004/2005. The sampling technique used is Simple Random Sampling. Sample was taken on 40 students within 8 classes. The data was then analyzed by using Multiple Linear Regretions. The result of research showed that there is positive correlation between psychological vitality and cognitive competence on biological learning of the X grade students of SMA Negeri 2 Sragen (r,ty = 0.424 with Fstatistic = 8'325 ) Ftabte (1,38; 0.0, = 4.10). Positive correlation was obtqin betyveen psychomotor competence and  cognitive competence onbiological learning(r,zy=0.346withF,so,;,,ir=5.163 )Ftabte(1,38;0.0s)=4.10. Thereis positive correlation between psychological vitality and psychomotor competence with cognitive competence on biological learning (R = 0.5036 with F,r,;,,i, = 6.285 ) Ftabte (2,37;0.05) = 3.25). psychic vititity is the iidependent variable giving a dominant cantribution to cognitive competence on biological with contribution of O2.St Vo.